Collection management and development : issues in an electronic era : proceedings of the Advanced Collection Management and Development Institute, Chicago, Illinois, March 26-28, 1993 - 4 0 16; Advanced Collection Management and Development Institute (1993 : Chicago, Ill.); 1948- Johnson, Peggy,;MacEwan, Bonnie; 5 (Chicago : American Library Association, 1994)
A collection of essays that were presented at the first Advanced Collection Management and Development Institute that was held at the Stouffer Riviere Hotel in Chicago from March 26 to March 28, 1993.
The coming of the millennium : is there a future of the research library? / Paul H. Mosher -- Staffing : the art of managing change / Nancy W. Ferguson -- Politics and policy from the trenches / Kathleen Zar -- Moving copyright to librarians' action agenda / Gloriana St. Clair -- Collection development and the Internet / Peggy Johnson -- Access, ownership, and the future of collection development / Ross Atkinson -- Financial issues for collection managers in the 1990s / Eugene L. Wiemers -- Indexing material budgets at Ohio State University / Gay Dannelly.
Includes bibliographical references (p. 142) and index.
Keywords: 2 -- 0; 6; Collection development -- Research libraries;Collection development (Libraries);Research libraries -- United States;United States -- Congresses.;Congresses.;Congresses.; 20; 2